Impact of Insurance Contract Implementation and Financial Performance on Company Value in the Insurance Sector - Hikmah, Fadillah Nur; Afif, Muhammad Nur; Melan, Maria Magdalena (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Financial performance is a description of the condition of a company that is analyzed to provide information about the work achievements and as a basis for evaluation and assistance in financial decision- making for the company. This research aims to determine the influence of the application of Statement of Financial Accounting Standards (Pernyataan Standar Akuntansi Keuangan/PSAK) 117 with financial performance variables, profitability, and solvency on the value of the company in the insurance sector. This study uses a quantitative descriptive method and the data used are secondary data obtained from reports or documents with the help of Eviews 12 software as a data processing tool. The population in this study is general insurance companies listed by the Financial Services Authority during the period 2018-2023, totaling 76 companies. Through purposive sampling method, 6 companies were selected as samples for a 6-year observation period. The results of the study show that Profitability does not affect the company value, while Solvency significantly influences the company value. Profitability and solvency moderated by PSAK 117 can moderate the company value.